Understanding the formation of phenolic monomers during fractionation of birch wood under supercritical ethanol over iron based catalysts. Issue 5 (October 2020) - Jogi, Ramakrishna; Mäki-Arvela, Päivi; Virtanen, Pasi; Kumar, Narendra; Hemming, Jarl; Russo, Vincenzo; Samikannu, Ajaikumar; Lestander, Torbjörn A.; Mikkola, Jyri-Pekka
Abstract: The liquefaction of biomass in ethanol, at the critical point, has high potential due to low temperature and pressure (243 °C, 63 bar) when compared with water (374 °C, 220 bar). The current study deals with the fractionation of birch wood powder which was liquefied under supercritical ethanol over acidic or non-acidic catalysts, 5 wt % Fe-Beta-H-150 and 5 wt % Fe–SiO2, respectively. Based on the results, the reaction mechanism for the formation of lignin degradation products was proposed. The main phenolic product was isoeugenol over 5 wt % Fe-Beta-H-150 while intermediate products, i.e. such as coniferyl, and sinapyl alcohol, 4-propenyl syringol, syringaresinol, as well as syringyldehyde reacted rapidly further. The thermodynamic analysis was performed by Joback approach and using Gibbs-Helmholtz equation supporting the obtained results. Highlights: Acidic 5 wt. % Fe-Beta-H-150 catalyst promoted the formation of isoeugenol. A non-acidic Fe-SiO2  and in the absence of catalyst the main products are sinapyl and coniferyl alcohol, respectively. Enthalpy and Gibbs free energy for each reaction and equilibrium constants were calculated with product analysis results.